eval_uation of IT Governance at Credit Union XYZ Financial Institutions Using COBIT 5 Framework - Vinsensius Rekat; Gunawan Wang (Publikasi Indonesia, 2024)
Since 2002, Credit Union XYZ has been utilizing information technology in its lending operations. However, the utilization of IT governance has not been optimal due to various weaknesses, obstacles, and issues such as server problems, downtime for maintenance, system change requests, human resources, and recurring IT-related problems. This research aims to assess the current IT governance capabilities at Credit Union XYZ. The method used is the COBIT 5 standard with a focus on the APO and DSS domains tailored to the existing issues. Data were collected through questionnaires distributed to the IT team and relevant stakeholders. The selected COBIT 5 processes include APO06 (Manage budget and costs), APO07 (Manage human resources), DSS01 (Manage operations), DSS02 (Manage service requests and incidents), and DSS03 (Manage problems). The eval_uation reveals a 1 level gap in IT governance capabilities, with the current level at level 2 in Credit Union XYZ, while the target is level 3 in the future. The researcher's recommendation to Credit Union XYZ is to align IT processes with the standards and regulations established by COBIT 5.